Factors influencing intention to use mobile banking in Bank Simpanan Nasional using modified technology readiness acceptance model (TRAM) - Nurdiana, Abdul Rani (2016)
The aspiration of this research is to study the factors that influence the intention to use mobile banking in Malaysian perspective by using integrated model TRAM. The theoretical framework of this research is the combination of technology readiness (TR) and technology acceptance model (TAM), where perceived usefulness completely mediates the impact of technology readiness towards the intention to use mobile banking. This research employed the full 16-item of technology readiness index (Parasuraman and Colby, 2014) to measure optimism, innovativeness, discomfort, and insecurity; whereas perceived usefulness and intention to use were adapted from Davis (1989) and Wang et al., (2006). Based on the research analysis, optimism and innovativeness have a positive effect on customer’s perceived usefulness of mobile banking. Whereas, discomfort and insecurity indicate a weak correlation towards perceived usefulness. On the contrary, perceived usefulness has a strong correlation in influencing the customer’s intention to use mobile banking. This research provides a useful understanding of customer’s perceived usefulness and their intention to use mobile banking.